Secondary mechanisms of injury and viable pathophysiological targets in intracerebral hemorrhage - Bautista, Wendy; Adelson, P. David; Bicher, Nathan; Themistocleous, Marios; Tsivgoulis, Georgios; Chang, Jason J. (Therapeutic advances in neurological disorders, 2021)
Intracerebral hemorrhage (ICH) can be divided into a primary and secondary phase. In the primary phase, hematoma volume is evaluated and therapies are focused on reducing hematoma expansion. In the secondary, neuroprotective phase, complex systemic inflammatory cascades, direct cellular toxicity, and blood-brain barrier disruption can result in worsening perihematomal edema that can adversely affect functional outcome. To date, all major randomized phase 3 trials for ICH have targeted primary phase hematoma volume and incorporated clot evacuation, intensive blood pressure control, and hemostasis. Reasons for this lack of clinical efficacy in the major ICH trials may be due to the lack of therapeutics involving mitigation of secondary injury and inflexible trial design that favors unilateral mechanisms in a complex pathophysiology. Potential pathophysiological targets for attenuating secondary injury are highlighted in this review and include therapies increasing calcium, antagonizing microglial activation, maintaining macrophage M1 versus M2 balance by decreasing M1 signaling, aquaporin inhibition, NKCCl inhibition, endothelin receptor inhibition, Sur1-TRPM4 inhibition, matrix metalloproteinase inhibition, and sphingosine-1-phosphate receptor modulation. Future clinical trials in ICH focusing on secondary phase injury and, potentially implementing adaptive trial design approaches with multifocal targets, may improve insight into these mechanisms and provide potential therapies that may improve survival and functional outcome.